Sistem Monitoring Lingkungan Wireless Berbasis Arduino - Febriyanto, Eko Didik, Heru Supriyono, ST. MSc. PhD (2017)
Wireless technology is now developing very rapidly, one implementation has been applied to the tools to monitor environmental conditions. Currently the tools to monitor the environmental conditions typically are placed in one place permanently. To overcome this problem researchers have an idea of research that aims to create a tool to monitor the environmental conditions that can be brought anywhere without the need for a permanent plug in place. In this study using arduino nano as a controller and two sensors as a signal input which reads environmental conditions. This tool is equipped with a sensor BMP180 to read the environmental conditions, such as temperature, barometric pressure and altitude. In addition, these tools are MQ-2 gas sensor used to detect the presence of gas levels in the environment around the tool. When detecting the presence of gas levels around the tool then the red LED will light up as an indication of gas. The way it works is installed on the system box Quad Copter to fly. After the sensor reads the data, arduino will transmit data using a telemetry module Kit 433 MHz transceiver. After than data will be received by the module Telemetry Kit 433 MHz receivers on the computer and sensor readings can be seen in the visual display. Data will be stored in the data logger in the form of files in ".txt" format. Keywords: Arduino, BMP 180, Gas Sensor MQ2, LED, Telemetry Kit 433 MHz, Quad Copter.